The Dynamics of Gastric Emptying and Self-Reported Feelings of Satiation Are Better Predictors Than Gastrointestinal Hormones of the Effects of Lipid Emulsion Structure on Fat Digestion in Healthy Adults—A Bayesian Inference Approach. Issue 4 (22nd February 2017) - Steingoetter, Andreas; Buetikofer, Simon; Curcic, Jelena; Menne, Dieter; Rehfeld, Jens F; Fried, Michael; Schwizer, Werner; Wooster, Tim J
Abstract: Background: Limited information exists on the relation between fat emulsion structure and its effect on the release of gastrointestinal hormones and feelings of satiation. Objective: We investigated the impact of fat emulsion droplet size, gravitational and acid stability, and redispersibility on gastrointestinal responses and sought to deduce the relative importance of the hormones ghrelin, cholecystokinin, glucagon-like peptide-1, and peptide YY (PYY) in controlling fat emptying and related satiation. Methods: Within a randomized, double-blind, 4-armed crossover study, an extensive data set was generated by MRI of gastric function, analysis of hormone profiles, and ratings of satiation in healthy participants [10 women and 7 men with a mean ± SD age of 25 ± 7 y and body mass index (in kg/m 2 ) of 22 ± 1] after intake of 4 different fat emulsions. Iterative Bayesian model averaging variable selection was used to investigate the influence of hormone profiles in controlling fat emulsion emptying and satiation. Results: The emulsion structure had a distinct effect on the gastric emptying (primary outcome), gastrointestinal hormone profiles, and ratings of satiation (secondary outcomes). Gravitational and acid stability were stronger modulators of fat emptying and hormone profiles than were emulsion droplet size or redispersibility. Cholecystokinin and PYY were most strongly affected by fat emulsion instability and droplet size. Although both hormones were relevant predictors of gastric emptying, only PYY was identified as a relevant predictor of satiation. Conclusions: This work indicates that evenly dispersed, stable, small-emulsion droplets within the stomach lead to prolonged gastric distension, longer ghrelin suppression, and accelerated fat sensing (cholecystokinin and PPY), triggering prolonged feelings of satiation. It suggests that the effects of emulsion instability and droplet size on energy consumption are best studied by assessing changes in gastric emptying and ratings of satiation rather than changes in venous hormone profiles. This trial was registered at clinicaltrials.gov as NCT01253005.